(untitled) (ModaPalavra e-periódico, 2016)
This study presents a review on the trend forecasting method developed for and applied by the FPLab research project. The method initially proposed as a conceptual model is of qualitative nature, involves inductive and deductive procedures, and relies on Human Sciences approaches and premises. More specifically, the main reference to the method is Grounded Theory of Glaser and Strauss (1967), which defines the need for hypothesis to arise from the data and rejects the procedures of going to the field merelyto confirm or reject hypothesis that where formulated priory to the field experience. The investment in such theory as research reference also influences the stages of data analysis –coding -, considered the most important phase of trend analysis forecasting. We have developed this method to the research-concerned group; however, one may apply it in other contexts with the goal of prospective research with the necessary adjustments.